2010
DOI: 10.1094/pdis-94-6-0717
|View full text |Cite
|
Sign up to set email alerts
|

BotryosphaeriaceaeSpecies Spore-Trapping Studies in California Vineyards

Abstract: The seasonal abundance of Botryosphaeriaceae spp. spores was studied in California vineyards by using glass microscope slides covered with petroleum jelly placed on grapevine cordons and Burkard volumetric spore traps at seven and two different locations, respectively. Correlation analysis was used to determine which meteorological variables (precipitation, relative humidity, temperature, and wind speed) influenced Botryosphaeriaceae spp. spore release. Among all variables, regression analysis resulted in a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 29 publications
2
75
2
Order By: Relevance
“…Overhead sprinklers are frequently used in South African nurseries (62) and other warm climates (H. Waite, personal communication) and are often considered a good method of irrigation provided the sprinklers have a uniform distribution pattern and are mounted high enough to clear the foliage (138); however, this method could enhance pathogen survival and dispersal and disease development (98), and drip irrigation is often used as the main source of irrigation once the vine root systems are established. A recent study demonstrated that overhead sprinkler irrigation can trigger Botryophaeriaeae spore release in some vineyard sites in California (201).…”
Section: Production Of Vinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Overhead sprinklers are frequently used in South African nurseries (62) and other warm climates (H. Waite, personal communication) and are often considered a good method of irrigation provided the sprinklers have a uniform distribution pattern and are mounted high enough to clear the foliage (138); however, this method could enhance pathogen survival and dispersal and disease development (98), and drip irrigation is often used as the main source of irrigation once the vine root systems are established. A recent study demonstrated that overhead sprinkler irrigation can trigger Botryophaeriaeae spore release in some vineyard sites in California (201).…”
Section: Production Of Vinesmentioning
confidence: 99%
“…A number of studies have, however, also shown that these fungi can infect directly through lenticels, stomata, or other openings on healthy plants (26,97,123). Species of Botryosphaeriaceae are able to produce pycnidia and pseudothecia on diseased wood or pruning debris from which propagules are released during wet, rainy weather (91,112,149,201,208). These propagules are then wind or splash dispersed by rain or sprinkler irrigation to infect wounds (91).…”
Section: Potential Inoculum Sources In the Grapevine Propagation Processmentioning
confidence: 99%
“…Spores of the Botryosphaeriaceae, including those of L. theobromae, emerge in a sticky matrix and are relatively large (the most common spores, conidia, range between 10-35 × 8-15 µm; [12]) and are naturally dispersed by wind and rain splash [6,16,[60][61][62]. Consequently spores are not expected to be spread over large distances or across geographic barriers and certainly not between continents.…”
Section: Discussionmentioning
confidence: 99%
“…They cause a range of symptoms, including leaf spots, fruit rots, dieback, perennial cankers, and eventual death of the plants, although symptoms vary according to the host species, cultivar and pathogen species (Alves et al 2005;Úrbez-Torres et al 2010). Yield losses caused in vineyards were estimated to be 4-20% in France and 25-30% in South Africa (Pearson & Goheen 1998;Larginon et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, artificially inoculated vine material was used in all of these studies and observations from naturally infected material have not been made. Further, although conidia have been detected by trapping in vineyards (Amponsah et al 2009;Úrbez-Torres et al 2010;Ridgway et al 2011;Valencia et al 2015), observation of cirrhi (a mucus-bound ribbon-like mass extrusion of conidia) from pycnidia on lesions in vineyards has not been reported.…”
Section: Introductionmentioning
confidence: 99%